Selpercatinib and capmatinib combination promotes sustained complete response in novel ISOC1-RET fusion lung cancer after resistance to RET inhibitor via MET amplification: Case Report - Caio Abner Leite; Raíssa Pierri Carvalho; Felipe Marques da Costa; Augusto Kreling Medeiros; Fabio Augusto Schutz; William Nassib William; William Nassib William (Frontiers in Oncology, 2023)
RET fusions occur in 1–2% of non-small cell lung cancer. Selpercatinib and pralsetinib are selective RET inhibitors with significant improvement of outcome in patients with tumor harboring RET fusion; however, resistance mechanisms appear frequently, mainly driven by MAPK pathway bypass, secondary RET mutations, or in 5% via MET amplification. Co-inhibition of RET and MET is a compelling strategy for overcoming MET-dependent resistance to RET inhibitors and potentially other inhibitors. To our knowledge, this is the first report of a novel ISOC1-RET fusion lung cancer with a durable complete response to selpercatinib, with resistance via MET amplification, which was overcome by the successful combination of selpercatinib and capmatinib.